Increased proportion of follicular helper T cells is associated with B cell activation and disease severity in IgA nephropathy - Du, Wanshan; Gao, Cai-Yue; You, Xing; Li, Liang; Zhao, Zhi-Bin; Fang, Mengting; Ye, Zhiming; Si, Meijun; Lian, Zhe-Xiong; Yu, Xueqing (Frontiers in Immunology, 2022)
IgA nephropathy (IgAN) is the most common primary glomerulonephritis, characterized by glomerular deposition of IgA immune complexes, mainly produced by B cells under the regulation of CD4+T cells. However, the alterations of specific CD4+T cell subsets and the mechanism of B cells activation in IgAN remain unclear. Therefore, we aimed to investigate the landscape characteristics and role of CD4+T cells in the progression of IgAN. We identified that the proportion of Th2, Th17 and Tfh (follicular helper T) cells in patients with IgAN was significantly higher than that of healthy controls (P < 0.05). Single-cell RNA sequencing of peripheral blood mononuclear cells (PBMCs) showed that Th cells and B cells in patients with IgAN were more activated. Correspondingly, multiplex immunohistochemistry staining of renal biopsy showed increased infiltration of CD4+T and B cells in the kidneys of patients with IgAN. The degree of infiltration was positively correlated with the degree of renal damage. Interestingly, the proportion of Tfh cells in peripheral blood was positively correlated with the severity of proteinuria. Moreover, the proximity position of Tfh cells and B cells suggested that cell-cell interactions between Tfh and B cells were happening in situ. Intercellular communication analysis also showed enhanced interaction between Tfh cells and B cells in IgAN. Our findings suggested that Tfh cells of patients possibly contributed to the progression of IgAN by activating B cells via cell-cell interactions and TNFSF14-TNFRSF14 may be an underlying signaling pathway.